2019
DOI: 10.1093/cdn/nzz049.p19-001-19
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Dietary Inflammatory Index and Biomarkers of Inflammation, DNA/RNA Oxidative Stress, Glycemic Control, and Blood Pressure in Adults with Type 2 Diabetes (P19-001-19)

Abstract: Objectives Nutrition plays a critical role in systemic inflammation regulation and the risk of developing inflammatory diseases such as type 2 diabetes (T2D). The Dietary Inflammatory Index (DII) is a non-invasive comprehensive literature-derived tool that evaluates the inflammatory potential of each individual's diet. The aim of this study was to assess the relationship between DII and biomarker of inflammation (CRP), DNA/RNA oxidative stress (8OHdG), glycemic control [HbA1c, glycated albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…21 Dietary inflammatory index (DII) is a goal standard index for estimation of the overall inflammatory and anti-inflammatory potential of the dietary intake. [22][23][24] Growing evidence has indicated that high inflammatory potential of diet plays a critical role in the development of dyslipidaemia, oxidative stress and inflammation. [25][26][27][28] What remains unclear to date is whether DII can modify the association between APOA2 −265T > C polymorphism and cardio-metabolic parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Dietary inflammatory index (DII) is a goal standard index for estimation of the overall inflammatory and anti-inflammatory potential of the dietary intake. [22][23][24] Growing evidence has indicated that high inflammatory potential of diet plays a critical role in the development of dyslipidaemia, oxidative stress and inflammation. [25][26][27][28] What remains unclear to date is whether DII can modify the association between APOA2 −265T > C polymorphism and cardio-metabolic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated protective effects of anti‐inflammatory diet on chronic diseases such as diabetes and metabolic syndrome (MetS) 21 . Dietary inflammatory index (DII) is a goal standard index for estimation of the overall inflammatory and anti‐inflammatory potential of the dietary intake 22‐24 . Growing evidence has indicated that high inflammatory potential of diet plays a critical role in the development of dyslipidaemia, oxidative stress and inflammation 25‐28 .…”
Section: Introductionmentioning
confidence: 99%